ANALISIS HIERARKI KEBUTUHAN PADA TOKOH LENA DALAM NASKAH DRAMA LENA TAK PULANG KARYA MURAM BATUBARA - Zahra Zhafirah Permana; Elsa Rahmadita (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to determine the hierarchy of needs experienced by the character Lena in the manuscript Lena Tak Pulang by Muram Batubara. Through a qualitative descriptive approach, this study classifies five hierarchies of needs according to Maslow including: physiological needs, needs for security, needs for love and belonging, needs for self-esteem, and needs for self- actualization. The results of the analysis found that the physiological needs of Lena's character were fulfilled or achieved while the other four needs were still not achieved or even not fulfilled, as a result Lena's character felt a lack of attention and recognition from her parents. From the conflict experienced by Lena's character, she has to struggle with her inner self to achieve other needs in the midst of emotional inability and a less favorable social environment. This research provides new things in the application of psychological theory in analyzing drama scripts, especially in understanding the emotional and social dimensions of the main character.